2015
DOI: 10.2209/tdcpublication.56.105
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytokeratin 14 and 19 in Process of Oral Carcinogenesis

Abstract: Cytokeratins (CK) are abundant in keratinized cells, particularly CK14 and CK19, which are expressed in stratified squamous epithelial cells. In this study, expression of CK14 and 19 was examined in human epithelial and dysplastic tissues. Surgical specimens from patients with clinically diagnosed oral leukoplakia or early cancer were stained with hematoxylin and eosin and classified into normal, low grade dysplasia (LGD), high grade dysplasia (HGD), or squamous cell carcinoma (SCC). The sections were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Thus, the general hair quality is believed to have some correlations to the keratin levels of HFORSC and HFIRSC. Keratin-14, a type I keratin in normal epidermis which is mainly expressed in the basal layer cell with fission and proliferation abilities, is of great importance in maintaining the proliferation and differentiation of skin basal layer cells and the integrity of cell morphology [ 31 , 32 ]. Keratin-15, as a sign of hair follicle stem cells, is specifically expressed in HFORSC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the general hair quality is believed to have some correlations to the keratin levels of HFORSC and HFIRSC. Keratin-14, a type I keratin in normal epidermis which is mainly expressed in the basal layer cell with fission and proliferation abilities, is of great importance in maintaining the proliferation and differentiation of skin basal layer cells and the integrity of cell morphology [ 31 , 32 ]. Keratin-15, as a sign of hair follicle stem cells, is specifically expressed in HFORSC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have revealed variability in ED grading [19,22,34,35], only a few studies have investigated supportive grading tests [36] and no studies have tested the actual effect of utilizing such tests or stains on examiners variability of grading epithelium of the upper aerodigestive tract. K19 immunoexpression was selected to be the adjunctive stain in grading process because its expression has shown a significant correlation with the extension of dysplastic cells within epithelial thickness [25,28,37]. K19 in the suprabasal region is accompanied by a delay of involucrin expression indicating a delay in commitment to terminal differentiation thus supporting that suprabasal K19 expression indicates increased premalignant potential [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin 19 (K19) is normally expressed in the basal cell layer or stem cells. Its expression in suprabasal locations in oral epithelium has been correlated with the presence and the grade of ED [24][25][26][27][28]. However, no previous studies have investigated the impact of K19 expression on reducing the variability of grading ED.…”
Section: Introductionmentioning
confidence: 99%
“…The non-keratinization marker CK13 is found in simple epithelium and some stratified epithelia 7) . Cytokeratin 17, which is found in simple epithelia and some stratified epithelia 1) , may indicate malignant transformation in oral epithelial squamous cells 21) . Here, the expression profiles of CK13, 14, 17, and 19 were investigated during a series of carcinogenetic processes using a rat model of 4-nitroquinoline-1-oxide(4NQO)-induced tongue cancer to determine whether these expression profiles could be used to assess the characteristics of epithelial dysplastic spread around a cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Low CK14 and high CK19 expression in early cancer and precancerous lesions could serve as indicators of malignant potential 21) . Hence, it is clear that change in the expression of cytokeratin 13 and 17 is related to carcinogenesis.…”
mentioning
confidence: 99%